Eclampsia Characteristics and Outcomes: A Comparison of Two Eras. (7th April 2013) - Schenone, Mauro H.; Miller, Dorothy; Samson, Jacques E.; Mari, Giancarlo
Abstract : Objective . To describe the trends in incidence, characteristics, and outcomes of women with eclampsia. Methods . We reviewed and abstracted data from medical records of all women diagnosed with eclampsia in our institution from August 1998 to April 2011. In addition to overall characteristics and outcomes, the cases were stratified by onset: antenatal versus postnatal and early (<32 weeks of gestation) versus late antenatal cases (≥32 weeks of gestation). Comparisons were made using chi-square, Fisher's exact, Mann-Whitney U, and t -tests. A two-sided P < 0.05 was considered statistically significant. Results . We identified 87 eclampsia cases out of 59, 388 deliveries; 62 cases were diagnosed before delivery, and 25 had a postnatal onset. Among the 62 antenatal cases, 41 were diagnosed before 32 weeks and 21 at or after 32 weeks of gestation. Antenatal cases had higher systolic (P = 0.03 ) and diastolic (P = 0.01 ) blood pressures, more abnormal dipstick-test proteinuria (P = 0.002 ), and lower platelet counts (P ≤ 0.001 ) than postnatal cases. Early eclampsia cases were complicated more often with HELLP syndrome than late eclampsia cases (P = 0.007 ). Conclusion . The occurrence of eclampsia has decreased over time. The earlier the onset is, the worse the outcome appears to be.